Association of Apolipoprotein E Polymorphisms and Risks of Ischemic Stroke in Chinese Patients with Type 2 Diabetes Mellitus - Na Wang; Qian Liu; Hui Liu; Xiao Cong; Hui Yang; Yang Yu; Yongtong Cao; Liang Ma (Journal of Diabetes Research)
Background. The apolipoprotein E (APOE) gene polymorphisms have been intensively studied in patients with type 2 diabetes mellitus (T2DM) and ischemic stroke (IS) in recent years. However, it is unclear whether APOE gene polymorphisms are correlated with increased risk for developing IS in T2DM patients. Thus, this study was designed to examine the association between APOE gene polymorphisms and risks of IS in Chinese patients with T2DM. Methods. This case-control study enrolled 243 subjects with T2DM as controls, and 210 subjects with T2DM complicated with IS as case patients. The genotypes were determined using real-time PCR while HbA1c and lipid levels were detected using commercially available kits. Results. The systolic blood pressure (SBP), diastolic blood pressure (DBP), and the proportion of patients with a history of hypertension were higher in the case patients than that in the controls. We confirmed that the ε2/ε3 genotype, as well as SBP and history of hypertension, was the independent risk factor for developing IS in T2DM patients. Conclusions. We conclude that the ε2/ε3 genotype might contribute to the increased risk for developing IS in Chinese patients with T2DM.